Multipurpose automatic Kerisik packaging machine - Sukarman, Muhammad Izwan; Hassan, Mohd Fahrul; Moktar, Muhammad Syukri Amri; Ramli, Mohamad Akmal; Jelani, Mohd Nashafizie; Ab Karim, Nurfarahnabila (Penerbit UTHM, 2017)
Automatic food packaging machine is a combination of mechanical and electrical components. This machine uses electrical power and pneumatic power as a major force for relative motion. The control system programmable logic control (PLC) is used as a controller for controlling the operation of the automatic packaging just ordered sequence program to the PLC only. Kerisik automatic packaging machine is a project designed that help entrepreneurs and small industries to enhance their business. Kerisik automatic packaging machine is equipped by electro pneumatic components that are controlled by the PLC control system. The improvement of the kerisik automatic packaging machine, the packaging can be reduced because the entire process including the filling and sealing process is done automatically.